GAMBARAN PENGETAHUAN DAN PELAKSANAAN HAND HYGINE OLEH TENAGA KESEHATAN PUSKESMAS RUMBAI BUKIT KOTA PEKANBARU TAHUN 2022 - Roni Saputra (Jurnal Keperawatan Abdurrab, 2023)
Hand hygiene is a general term that applies to both hand hygiene with antiseptic soap and antiseptic handrub. Hand hygiene is one of the effective steps to break the chain of infection transmission, infection prevention and control absolutely must be done by nurses, doctors and all people involved in patient care. The purpose of this study was to determine knowledge about the implementation of hand hygiene by health workers at the Palas Health Center in 2022. This study was a quantitative study with a descriptive design. The population in this study were all health workers who were at the Rumbai bakti Palas Public Health Center in Pekanbaru, which amounted to 30 people. The sample in this study amounted to 30 people. Based on the results of the study that of the 30 respondents at the Rumbai Bukit Health Center, the majority of the knowledge of hand hygiene practice for health workers was good with a total of 29 respondents (96.7%) stating that the knowledge of implementing hand hygiene for health workers was sufficient with 1 respondent (3.3%) ), The results of the study based on the checklist, it was found that of the 30 respondents at the Rumbai Bukit Health Center, Palas the majority of the hand hygiene compliance checklist was good with a total of 30 respondents (100%). Suggestions from this study are expected to provide information to health workers about the implementation of hand hygiene.